Investigation of laser speckle noise suppression by using polymer-stabilized liquid crystals within twisted nematic cell. (15th February 2017) - Lin, Ja-Hon; Chang, Shu-Chun; Li, Yi-Han; Chien, Cheng-Yen; Chen, Chien-Hsing; Lin, Yi-Chin; Wu, Jin-Jei; Tsay, Shwu-Yun; Chen, Yao-Hui
Abstract: We propose a robust method to suppress laser speckle using a polymer-stabilized liquid crystal (PSLC) device with high initial transmittance. With applied voltage, a large modulation depth has been produced through light scattering because of the refractive index mismatch between the rotated nematic liquid crystals and the polymer networks. By using PSLCs with 5 wt % monomer, a speckle noise reduction rate of approximately 54.7% can be achieved with an applied voltage of 6 V. The lowest speckle contrast of approximately 0.025 with relatively high discrimination from the projected AF image has also been demonstrated through a wedge PSLC cell.